Advanced Smart Material Based Nano sensors for Viral Detections (Journal of Fiber Bioengineering and Informatics, 2023)
Now-a-days, researchers focus on the use of smart materials due to their multiple functional capabilities.A “smart material” is one having a nano level structure that can responds in a specialised and controlledway to influence on its sensing mechanisms. Due to the multiple properties of smart materials, theyhave a great influence on current analytical methods and diagnostic strategies by reorganizing thesensing modules for nano-sized objects (protein biomarkers and viruses) and biomolecules detection.Incontestably, current sensing mechanisms need a continuous update for addressing the growing challengesin the field of diagnosis for viruses because these viruses altered and spread rapidly from person-topersons. It becomes critical to take into consideration several factors for viral diagnosis ranging from thetype and quality of specimen collected, mode of transport, time of specimen collection, level of accuracyor specificity, viral detection sensitivity, and the type of diagnostic method used. In this review, webriefly explained the principle and different types of smart materials being used for diagnosing infectiousviruses. The development in the field of smart material based nano sensors with resource-scarce settings isfurther discussed and elaborated the pros and cons of current methods for viral detection as a conclusionand future perspective.
Keywords: Viruses; Smart Materials; Nanosensors; Graphene; Sensing Mechanism